Rgn -Verslag oor godsdiens, tussengroepverhoudinge en maatskaplike verandering in Suid-Afrika - Merwe, P. J. van der (Hervormde teologiese studies, 1986)
The HSRC Report on religion, intergroup relations and social change in South Africa This article deals with the HSRC Report Religion, intergroup relations and social change in South Africa of 1985. The report is found to be well researched. A basic statement thereof is that religion functions in an ambivalent manner: It may transcend group interests for the sake of broader or national interests and thus facilitate reconciliation or it may become a captive of group interests and by legitimising group perceptions and claims, contribute to intergroup tension. Despite the Committee's claim to a scientific approach to religion, the report displays a natural theological aspect.